Pre-treatment, Germination and Growth Performance of Detarium microcarpum Seeds in three Planting Media - G. Dachung; A. B. Tyolumun; D. O. Ekhuemelo (Journal of Applied Sciences and Environmental Management, 2023)
Effect of 20%, 40% and 60% sulphuric acid concentrations on the pretreatment of Detarium microcarpum and seedling growth was studied using standard techniques. Seeds were collected and tested by floating. Results showed that seeds treated with 40% H2SO4 for 10 and 30 mins planted in river sand; 60% H2SO4 for 30 mins planted in top soil and those planted in untreated seeds had the highest (4) germination. Germination percentage of was highest (80%) with 40% H2SO4 treated seeds for 10 and 30 mins planted in river sand; control (river sand, river sand + top soil); 20% H2SO4 for 10 mins planted in top soil and 60% H2SO4 for 30 mins planted in river sand. Emergence index and emergence rate index of seeds followed same trend as germination percentage of seeds. The highest mean (16 cm) height of seedlings was recorded from river sand without H2SO4 seed treatment (control).Mean values of collar diameter, leaf area and number of leaves also follow same trend ofseedling height. There were no significant differences (p > 0.05) in seedling height, collar diameter, leaf area and number of leaves among seeds grown in different media and control. Seeds treated with 40% H2SO4 and plated in river sand had the highest number of germinations and river sand was the best media of growth.